Robert E. Howard’s critics and the question of racism - Garstad, Benjamin (My University, 2016)
Race seems to be the perennial hot potato of Robert E. Howard scholarship. The sentiments of a white Texan of the 1920s and '30s are there in Howard's writing and demand some kind of comment in the face of much-changed prevalent attitudes. Some readers have attempted to exculpate their literary hero by minimizing his racism and marginalizing or even erasing the evidence of it in his fiction. Others have conceded that Howard was a man of his time, but insisted that his skill as a writer compensates for his distasteful opinions. In both cases we hear the voice of the fan defending the object of his enthusiasm, but there are encouraging signs that a more detached critical stance is beginning to assert itself. And this analytical approach is just what is necessary if we are to shift the question from whether or not there is racism in Howard to how race functions in Howard's fiction and imbues it with some of its fundamental concerns, its energy, and its sincerity.
Keywords: Robert E. Howard; racism; fiction; race; writer; 1920s; Texan; critics; concerns; opinions